Impact of Shatavari (Asparagus racemosus) Root Meal Supplementation on Growth Performance, Haematology and Carcass Quality of Broiler Chickens - Verma, Raj Kapoor; Pramanik, Partha Sarathi; Singh, Kunwar Dhananjay; Verma, Ajeet Kumar; Singh, Shailendra; Kumar, Abhishek; Gupta, Nitish (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The goal of this study was to evaluate the effects of Shatavari (Asparagus racemosus) root meal supplementation on the growth,  haematology and carcass quality of broiler chickens. Two hundred day-old chicks (Vencobb 400) were randomly divided into four  groups with 50 chicks in each using two replicates each of 25 chicks under completely randomized design. Control group TC was fed  commercial diet without Shatavari root powder, while group T1, T2 and T3 were fed commercial diet supplemented with 0.5%, 1.0 %  and 1.5% Shatavari root powder, respectively, for 42 days. The results showed that T2 had the highest body weight (2547.76 g), followed  by T1, TC and T3. The TC group exhibited the highest overall feed intake (4339.64 g), followed by T1, T2, and T3. At 42nd day of treatment,  the mean Hb concentration of the T2, T3, and T1 groups of birds was considerably greater and TLC was lower (p
Keywords: Broiler chicken; Carcass quality; FCR; Haematology; Shatavari root powder; Supplementation